Gonadotropin releasing hormone agonist triggering for in vitro maturation cycles. (27th May 2022) - Hershko Klement, Anat; Navve, Daniella; Ghetler, Yehudith; Wiser, Amir; Shavit, Tal; Weitzner, Omer; Shulman, Adrian
Abstract: The objective was to evaluate the outcomes of in vitro maturation (IVM) cycles using gonadotropin releasing hormone agonist (GnRH-ag) triggering. A retrospective cohort of IVM cycles from January 2015 to December 2019 in a single university-affiliated centre was examined. Main outcome measures were: (i) IVM maturation rate; and (ii) IVM maturation result. Secondary outcome measures were: (i) metaphase II (MII) rate on the day of egg retrieval; (ii) final MII maturation rate; and (iii) pregnancy rates. A total of 98 IVM cycles were performed during the study period: 50 (51%) were triggered with GnRH-ag (17 received FSH priming and 33 did not) and 48 cycles (49%) were triggered by hCG (37 with FSH priming and 11 without). A significant ( p = 0.01) difference was noticed in maturation rate on egg retrieval day, in favour of the GnRH-ag group, although not in the final maturation rate achieved. Pregnancy rates were comparable between treatment sub-groups. GnRH-ag triggering in IVM cycles is an optional triggering mode and can be considered an acceptable option, especially when fertility preservation is a concern. GnRH agonists resulted in higher maturation rate on day of oocyte retrieval, but no difference in the total maturation rate.